1995
DOI: 10.1016/s0140-6736(95)90008-x
|View full text |Cite
|
Sign up to set email alerts
|

Is hyperhomocysteinaemia a risk factor for recurrent venous thrombosis?

Abstract: Please be advised that this information was generated on 2018-05-12 and may be subject to change.11 Snyder PJ, Utiger RD. Response to thyrotropin-releasing hormone (TRH) in normal man. J Clin Endocrinol Metab 1972; 34: 380-85. 12 Rooney S, Marino P, Gobrau L, Gross I, Warshaw J. Is hyperhomocysteinaemia a risk factor for recurrent venous thrombosis? M artin den Heijer, Henk J Biom , Wim B J G errits, F rits R Rosendaai, Hans L H aak, P ie rre W W ijerm ans, Gerard M J Bos SummarySeveral studies have shown a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
143
1
6

Year Published

1995
1995
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 337 publications
(157 citation statements)
references
References 13 publications
7
143
1
6
Order By: Relevance
“…Thus the prevalence was higher in males as compared to females. This is consistent with finding in other studies [5,6,8].…”
Section: Percentage Of Patientssupporting
confidence: 94%
See 2 more Smart Citations
“…Thus the prevalence was higher in males as compared to females. This is consistent with finding in other studies [5,6,8].…”
Section: Percentage Of Patientssupporting
confidence: 94%
“…Elevated homocysteine concentrations have been found in 40% of patients with vascular disease and 35% of patients with venous thromboembolism [5]. A study by Den Heijer M showed a prevalence of hyperhomocysteinemia as 10% [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the study by Falcon et al (1994) and Fermo et al (1995), the patients were very young (mean age 33 years), whereas Bienvenue et al (1993) had a control group with mean age 33 years and while the patients' mean age was 40 years. Den Heijer et al (1995) included patients only with recurrent thrombosis. In these four studies, patients with thrombosis at different locations were included, whereas in the study by Amundsen et al (1995) only patients with deep venous thrombosis were included and the patients had a mean age higher than in the other studies.…”
Section: Discussionmentioning
confidence: 99%
“…20 We extended our patient group with 60 patients with documented premature cardiovascular disease. 13 To equalise the male ± female ratio between the patient and control group, all 280 male controls from a second population-based control group 21 were included.…”
Section: Study Populationmentioning
confidence: 99%